2021
DOI: 10.53400/mimbar-sd.v8i1.30897
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Predict-Explain-Observe-Discuss-Explain (PEODE) Based Laboratory Work Activities on Pre-Service Science Teachers’ Science Process Skills

Abstract: This research aims at investigating the effectiveness of the Predict-Explain-Observe-Discuss-Explain (PEODE) based laboratory work activities on pre-service science teachers’ science process skills. A quasi-experimental research model with pre- and post-test via control group was employed in the research. The semi-experimental study was based on 46 pre-service science teachers enrolled in the primary Science Education Program a state university. In the research, randomly selected two groups were used, one expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In SMCT Scoring, the criteria and scores included in a previous research conducted by Coştu (2021) were used. Since the SMCT consists of two phases, second phase need to be analysed in order to evaluate which category is appropriate for given answer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In SMCT Scoring, the criteria and scores included in a previous research conducted by Coştu (2021) were used. Since the SMCT consists of two phases, second phase need to be analysed in order to evaluate which category is appropriate for given answer.…”
Section: Discussionmentioning
confidence: 99%
“…This result also supports the findings of previous similar studies. Such as; Coştu (2021) stated that POE-DE supported laboratory studies are effective in increasing pre-service teachers' academic achievement, scientific process skills, conceptual understanding and interpretation of daily life problems. Wulandari et al (2017) found that students can develop their critical thinking skills effectively by using the discussionenriched POE method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation